Extended generalized Darboux transformation to hybrid rogue wave and breather solutions for a nonlinear Schrödinger equation - Li, Bang-Qing; Ma, Yu-Lan (Applied mathematics and computation, 2020)
•An extended generalized Darboux transformation method is proposed.•Three types of hybrid rogue wave and breather solutions are obtained for a classical nonlinear Schrodinger equation.•The control and interaction of the hybrid wave solution are graphically demonstrated.•An exact link is established between the hybrid solutions and the rogue wave solutions. An extended generalized Darboux transformation method is proposed to construct the hybrid rogue wave and breather solutions for a classical nonlinear Schrödinger equation. Three types of hybrid wave solutions are obtained: (i) the hybrid first-order rogue wave and breather; (ii) the hybrid second-order rogue wave and first-order breather; (iii) the hybrid first-order rogue wave and second-order breather. These solutions are novel and can be used to investigate the dynamical characteristic of the hybrid rogue waves and breathers. The control and interaction based on the parameters of the hybrid wave solution are graphically demonstrated. An exact link is established between the hybrid solutions and the rogue wave solutions via setting the parameter at special value.